Social Norms and Legal Norms: A Comprehensive Study Of Their Differences, Functions, and Interrelationships in Society - Wahida Ariyanti Nasution; Nurlila Lila Pratiwi (Program Pascasarjana UIN Sumatera Utara Medan, 2024)
As social beings, humans can fulfill their own needs without interacting with others, so rules are needed to govern communal life. These rules are known as social norms, which are normative and motivating guidelines for behavior that create order and protect human interests. Social norms grow and develop along with the dynamics of community life and function as a means of social control to prevent conflicts of interest. According to Sudikno Mertokusumo, social norms consist of four types: religious norms, moral norms, politeness norms, and legal norms. Religious norms stem from belief in God and regulate human relationships with the Creator, others, and oneself. Moral norms originate from the human conscience, encouraging good behavior and eliciting regret when violated. Politeness norms arise from customs and traditions within society, aimed at maintaining social harmony. Meanwhile, legal norms are official rules established by the state with strict and enforceable sanctions. These four norms are interrelated and inseparable because together they create order and balance in social life.